Pembuatan Aplikasi Konversi Sederhana Menggunakan GUI Berbasis Python di SMK Puspa Bangsa Banyuwangi - Ana Fauziah; Hermanto Hermanto; Rina Silpiana (Pakis Journal Institute, 2024)
The impact of the development of the Industrial Revolution 4.0 in the world of work globally triggers the demand for Human Resources (HR) who have technological expertise. Technology integration in the education sector through learning media can be done as an effort to prepare graduates who can answer these challenges. Graphic User Interface (GUI) based learning media can be a way to introduce and increase digital literacy while increasing student interest in learning. The service activity is in the form of digital training related to the topic of unit quantity measurement in the form of a simple GUI-Python-based conversion application. This activity is expected to provide new insights related to programming and digital platforms and train students' computational thinking skills. The implementation of the service involved students of SMK Puspa Bangsa Banyuwangi as participants. The presentation method includes the delivery of introductory material and practice designing applications. The results of the service showed that around 80% of the participants were able to display, run and modify the conversion application.